1993
DOI: 10.1080/02678299308026445
|View full text |Cite
|
Sign up to set email alerts
|

A new type of electrohydrodynamic instability in nematic liquid crystals with positive dielectric anisotropy

Abstract: A new type of electrohydrodynamic instability originally reported in nematic liquid crystal mixtures with positive dielectric anisotropy and as moderately thick samples is further studied. The ability of homogeneously aligned nematics with positive dielectric anisotropy, in the presence of a magnetic field, to exhibit Williams domains as a threshold effect is numerically investigated. The variation of the threshold voltage for domain formation and dielectric alignment with dielectric anisotropy is calculated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recent experiments on liquid crystal nanocomposites have shown that an anchoring transition from planar to homeotropic anchoring induced by the presence of nanoparticles can enable electroconvection as well . This behavior of a uniform (surface-induced or field-induced) reorientation followed by EC is different from the instabilities, which may appear below the Fréedericksz threshold in materials with small positive Δε. However, an analogue case of indirect induction of dissipative structures has been observed for the opposite signs of the electric anisotropies and initially homeotropic alignment (−, +, h), where a Fréedericksz transition to the planar state (−, +, p) at a threshold voltage U F precedes an instability of the Carr–Helfrich type at a critical voltage U c > U F . In the latter case (no common in-plane orientation but local symmetry breaking through the in-plane component of the director for U > U F ), the induced convection rolls were observed to form striped patches with different alignment and were described as “quasi-anisotropic electroconvection” …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments on liquid crystal nanocomposites have shown that an anchoring transition from planar to homeotropic anchoring induced by the presence of nanoparticles can enable electroconvection as well . This behavior of a uniform (surface-induced or field-induced) reorientation followed by EC is different from the instabilities, which may appear below the Fréedericksz threshold in materials with small positive Δε. However, an analogue case of indirect induction of dissipative structures has been observed for the opposite signs of the electric anisotropies and initially homeotropic alignment (−, +, h), where a Fréedericksz transition to the planar state (−, +, p) at a threshold voltage U F precedes an instability of the Carr–Helfrich type at a critical voltage U c > U F . In the latter case (no common in-plane orientation but local symmetry breaking through the in-plane component of the director for U > U F ), the induced convection rolls were observed to form striped patches with different alignment and were described as “quasi-anisotropic electroconvection” …”
Section: Discussionmentioning
confidence: 99%
“…According to this standard model, two types of stationary patterns may exist depending on the frequency f of the applied ac voltage relative to a cutoff frequency f c ; for f < f c (conductive regime), only the charges oscillate with the voltage, while, for f > f c (dielectric regime), the director and the flow velocity change with the field direction. ,,, EC can also be observed under conditions where the feedback loop leading to instability is not obvious. For example, (−, +) materials with initial homeotropic alignment may show a field-induced transition (Fréedericksz transition) from (−, +, h) to (−, +, p) at a threshold voltage U F and an indirect transition to EC at voltages U > U F . Patterns observed in the case (−, +, p) may also appear for slightly positive Δε (+, +, p) at U < U F . More recently, it was recognized that the positive feedback loop yielding an instability appears not only in (−, +) materials with initial planar alignment (−, +, p) but also in (+, −) materials with an initial homeotropic alignment (+, −, h), (Figure f). Thus, the comprehensive model of standard electroconvection (s-EC) can generally be applied when Δε and Δσ have opposite signs. However, clearly different patterns and distinguished stability conditions can appear for (−, −) compounds and for (+, +) compounds with large dielectric anisotropy, where no instability was initially expected .…”
Section: Introductionmentioning
confidence: 99%